MANAGEMENT OF NON COMMUNICABLE DISEASES BY SIDDHA SYSTEM - Lekha, *G. S.; Sathiyarajeswaran, P. (AYUSHDHARA, 2015)
Background: Siddha System is a Philosophy based Medicine that deals with Holistic approach to health. Basically it’s a way of life that emphasizes Positive health. The essential life style for healthy living has been formulated in Siddha system of Medicine, according to the Geographical and Seasonal variations. As per Siddha concept, there is vitiation of three humours namely Vatham, Pittham and Kapham because of food habits and actions. This Paper addresses the problem of Non Communicable Diseases in this decade and discuss about its prevention by means of health measures in Siddha System. The measures for the Management of NCDs includes Regular Physical activity, Balanced diet and liquor, Regular sleep, Stress-free life, Pursuance of hygienic measures described in Siddha Literatures, Cessation of habits like Smoking and Alcohol consumption and then acclimatization of body to climatic variation. Aim & Objective: The rationale of this paper is to highlight the extent of the problem and threats posed by the life style modification in current scenario, and finally address the way of intervention by means of Siddha Principles. Conclusion: As the current scenario of life-style results in multiple complications like Physical and Metabolic derangement of the body, the follow up of rules and regulations (Daily and Seasonal regimen) mentioned in Siddha System is the proper way for the prevention and Management of NCDs.